Improving Children's Language Development By Storytelling Method Through Series Images In Group B3 Kindergarten: Literature Study: Meningkatkan Perkembangan Bahasa Anak Dengan Metode Bercerita Melalui Gambar Seri Di Kelompok B3 Tk: Studi Literatur - Fitria Sari; Putri Riyandini (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2020)
This research is attracted by the ineffective language development of children. This is because less of children stimulation to reveal the language skill. Therefore, it is important to have the media that can increase the development of children language like media of picture series. The aim of this study was to know the increasing of children language development.The kind of this research was literatur research. This study did by seeing many of studied that relevant with this research. In this research, the researcher took the result of comprising topic from 7 journals, 3 of books, and 4 of thesis that connected with story of picture series method.The result of this research showes the children language development was increase with story of picture series method. Based on the evidance, the researcher found out three of main results. They are increase the listening skill of children, improve the speaking skill of children, and enhance the reading skill of children.